RENAL CYST IN DOGS – AN IMAGING APPROACH - Sorin Marian Mârza; Robert Cristian Purdoiu; Radu Lăcătuș; Felix Daniel Lucaci (Agricultura)
The aim of this paper is to provide a comprehensive imaging-based approach to the diagnosis and evaluation of renal cysts. The study focuses on the case of a Yorkshire Terrier dog, which underwent a detailed imaging examination, including ultrasonography, radiographs and computed tomography (CT) scanning, to assess the renal condition. A comprehensive abdominal ultrasound was done, which revealed significant anechoic fluid-filled distension at the level of the right kidney. Radiographs demonstrated soft tissue opacity in the mid-abdominal region, and computed tomography (CT) imaging confirmed a distension of the right renal pelvis with clear demarcation from renal parenchyma. Differential diagnoses such as hydronephrosis and renal neoplasms were considered; however, renal cysts should also be prioritized when ultrasonography features revel a round structure with hyperechoic wall, anechoic content and well demarcation from renal pelvis.